UPAYA GURU PAI DALAM MENANAMKAN SIKAP DISIPLIN DAN TANGGUNG JAWAB PESERTA DIDIK DI SMPN 4 RAWA PITU, LAMPUNG - Khalimatur Rahmah; Muhammad Hanif; Moh. Eko Nasrullah (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The condition of the students' attitude of discipline and responsibility can be seen from the daily life of students during the learning process. When viewed from the daily lives of students when carrying out the learning process, it can be said that the condition of the state of student discipline and responsibility is still very lacking. This condition can be seen from the lack of time for students to come to school, there are still students who litter, and there are also students who do not use school attributes completely. Various examples of student circumstances, it is said that the students still have not applied the attitude of discipline. This type of research is qualitative. Using primary and secondary data obtained through observation, interviews, and documentation. Analysis technique with data reduction, data presentation, and verification. The results of the study are the conditions of discipline and responsibility as seen from the factors of obedience to learning, the tasks given, the use of facilities and the use of time at school. Then the teacher's efforts are getting used to coming on time, praying together, getting used to implementing religious orders in daily activities. The supporting factors experienced are good cooperation from parents, the inhibiting factors are the community environment and friendship.